2013
DOI: 10.1080/09297049.2012.713466
|View full text |Cite
|
Sign up to set email alerts
|

Higher functioning children with prenatal alcohol exposure: Is there a specific neurocognitive profile?

Abstract: Recent attempts to identify a neurocognitive profile of children with prenatal alcohol exposure (PAE) have led to an emerging "generalized deficit" conceptualization marked by diffuse information processing and integration difficulties as opposed to a specific profile. This study examines whether this conceptualization can be extended to higher functioning children with PAE who are without intellectual disability and addresses several limitations of previous research. One hundred twenty-five children aged 6-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…Rasmussen et al (2013) supported this argument by demonstrating greater differences between FASD and comparison groups on complex tasks that require both inhibition and switching, compared to tasks that only require inhibition. These findings are also consistent with prior research showing that children with FASD, compared to children without FASD, experience more pronounced challenges on set shifting (d= 0.78) compared to auditory working memory (d=0.50) tasks (Quattlebaum and O'Connor 2013). Thus, children and adolescents with FASD may demonstrate more profound deficits on set shifting tasks, as these tasks draw on a variety of cognitive abilities, each of which independently present difficulty, and combined may pose cumulative impairments.…”
Section: Differential Ef Deficitssupporting
confidence: 89%
See 1 more Smart Citation
“…Rasmussen et al (2013) supported this argument by demonstrating greater differences between FASD and comparison groups on complex tasks that require both inhibition and switching, compared to tasks that only require inhibition. These findings are also consistent with prior research showing that children with FASD, compared to children without FASD, experience more pronounced challenges on set shifting (d= 0.78) compared to auditory working memory (d=0.50) tasks (Quattlebaum and O'Connor 2013). Thus, children and adolescents with FASD may demonstrate more profound deficits on set shifting tasks, as these tasks draw on a variety of cognitive abilities, each of which independently present difficulty, and combined may pose cumulative impairments.…”
Section: Differential Ef Deficitssupporting
confidence: 89%
“…EF deficits are part of the core of the neurobehavioral phenotype of FASD (Nash et al 2015). Understanding the role of EF is important because these functions pervade many neuropsychological tasks, contributing to performance deficits across neurocognitive domains (Quattlebaum and O'Connor 2013).…”
mentioning
confidence: 99%
“…Though the field has yielded mixed results, our findings are consistent with studies that have demonstrated comparable levels of cognitive deficits between children with the physical features of FASD (e.g., FAS and pFAS) and those without physical features (e.g., ARND), suggesting that the degree of deficits observed following PAE may occur independently from any physical effects (Green et al 2009b;Mattson et al 1997Mattson et al , 1998Quattlebaum and O'Connor 2012). Alternatively, Astley's (2010) large scale cohort in Washington found a linear trend differentiating cognitive functioning among individuals with ND/AE, SE/AE, and FAS/pFAS, and Chasnoff et al (2010) similarly found differences in functioning between children with FAS compared with those with pFAS and ARND.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, deficits in visuospatial processing (using other measures) have previously been identified as particularly affected by PAE (Korkman et al 2003;Mattson et al 1998;Pei et al 2011), even after accounting for IQ (Quattlebaum and O'Connor 2012). However, one study found children with FASD performed similarly to IQ-matched controls on a visuospatial processing task (Vaurio et al 2011), and another found no significant group differences in this area using the same NEPSY-II subtest ).…”
Section: Relative Cognitive Strengthsmentioning
confidence: 90%
See 1 more Smart Citation